The Effect Of Growing Cells And In-Situ Biotransformation Of 2,6,6-Trimethylcyclohex-2-Ene-1,4-Dione Towards Products Formation - Hari, Siva Sree (Universiti Sains Malaysia, 2017)
Actinol (ACT) is the substrate needed for the synthesis of optically active xanthophylls, xanthoxin and zeaxanthins as well as aroma constituent of tobacco and saffron can be produced by the reduction of ketoisophorone (KIP) with high yield and enantioselectivity. The ACT can be produced from the biotransformation of KIP. The biotransformation of KIP forms levodione (DOIP), which is intermediate before further reduction into ACT. The biotransformation of KIP was studied during the growth phase of S. cerevisiae with the presence and absence of glucose. During the growth phase of S. cerevisiae, the biotransformation of KIP was only able to produce intermediate and the product was yet to be formed. The rate of biotransformation of KIP was faster with the presence of glucose. This was because presence of glucose increases the concentration of NADH and NADPH which was the essential cofactor needed for biotransformation of KIP. Thus, the rate of reduction of KIP was higher resulting in higher concentration of DOIP. When the rate of biotransformation was high, the production of ACT will also be faster. Therefore, the presence of glucose was important for the biotransformation of KIP.